Amikacin and bacteriophage treatment modulates outer membrane proteins composition in Proteus mirabilis biofilm - Agnieszka Maszewska (Nature Portfolio, 2021)
Abstract Modification of outer membrane proteins (OMPs) is the first line of Gram-negative bacteria defence against antimicrobials. Here we point to Proteus mirabilis OMPs and their role in antibiotic and phage resistance. Protein profiles of amikacin (AMKrsv), phage (Brsv) and amikacin/phage (AMK/Brsv) resistant variants of P. mirabilis were compared to that obtained for a wild strain. In resistant variants there were identified 14, 1, 5 overexpressed and 13, 5, 1 downregulated proteins for AMKrsv, Brsv and AMK/Brsv, respectively. Application of phages with amikacin led to reducing the number of up- and downregulated proteins compared to single antibiotic treatment. Proteins isolated in AMKrsv are involved in protein biosynthesis, transcription and signal transduction, which correspond to well-known mechanisms of bacteria resistance to aminoglycosides. In isolated OMPs several cytoplasmic proteins, important in antibiotic resistance, were identified, probably as a result of environmental stress, e.g. elongation factor Tu, asparaginyl-tRNA and aspartyl-tRNA synthetases. In Brsv there were identified: NusA and dynamin superfamily protein which could play a role in bacteriophage resistance. In the resistant variants proteins associated with resistance mechanisms occurring in biofilm, e.g. polyphosphate kinase, flagella basal body rod protein were detected. These results indicate proteins important in the development of P. mirabilis antibiofilm therapies.